Vaccine development and delivery strategies - A glimpse - Rashmi P; Madhavi BLR (Journal of Vaccines and Immunology - Peertechz Publications, 2021)
Vaccines are one of the oldest biological products which are most successful in modulating immune response against various life-threatening infectious diseases. Currently, there are many advancements in the designing and delivery of vaccines. Starting from the use of live attenuated and dead microbes as vaccines, to the stage of mapping antibodies using various software and algorithms for designing desired vaccine, the journey has taken many turns in the last two centuries. Current write up gives a glimpse of various developments in the development of vaccines as well as delivery strategies like use of immunoinformatics, artificial intelligence and efforts made towards the delivery of vaccines using nanoparticles, vectors, hydrogels as adjuancts.